Parents' Accompanying to Identify Special-Needs Children in Depok, Indonesia. - Suharsiwi; Pandia, Weny Savitry S.; Ruwinah, Ruwinah; Yumna, Laila (CV. BImbingan Belajar Assyfa, 2023)
The issue of detection services for children with special needs in Indonesia still merits attention, as it necessitates intensive treatment to enhance parents' ability to identify their children with growth and development issues. Regarding this topic, parents need a wealth of knowledge and skills. Community Service in Depok assists families in identifying children with special needs. Participants in the brief course must understand the characteristics of children with special needs. The goals of community service activities are as follows: a) conducting training activities on the characteristics of ABK, and b) conducting child development screening activities for the